Comprehensive review on Rabri -A traditional heat desiccated product - Meena, Sunil; Arvind; Meena, Ganga Sahay; Dinesh Chandra Rai; Kaushik Khamrui (Indian Journal of Dairy Science, 2022)
Rabri is a traditional Indian dairy product, manufactured by the concentration of sugar -containing milk via evaporation, maintaining slow heating conditions. It contains several layers of malai (clotted cream), formed via air cooling the surface of milk and continuous removal of formed layer which represents its typical attribute as well. It possesses a sweet taste and cooked flavor still, it may be infused with additional flavors, color, fruits and nuts for garnishing to enhance its sensory attributes. The physico-chemical, sensory and textural properties of rabri vary with the locality, type of milk used and the method employed for its preparation. This review briefly discusses the effect of different types of milks and manufacturing processes on chemical composition and typical sensory attributes of rabri. Recent innovations and advances in mechanization in rabri manufacturing,  microbial quality,  the problem of adulteration, shelf-life enhancement through the use of different packaging materials and fortification of rabri with different non-dairy ingredients and calorie reduction strategies have also been emphasized.